Contestation, instrumental resistance and strategic conformation within the diagnostic process of gender dysphoria in Portugal - Hilario, Ana Patricia (2017)
This article aims to provide insights into the ways in which trans people (i.e. those whose gender identity or expression do not align with their assigned sex at birth) in Portugal make sense of the diagnosis of gender dysphoria. Drawing upon in-depth interviews with 10 trans men and 9 trans women carried out by the TRANSRIGHTS team, we identified three major themes: (a) contestation of gender dysphoria as a (mental) illness, (b) instrumental resistance to complete demedicalisation of gender dysphoria and (c) strategic conformation to gender essentialism within the diagnostic process of gender dysphoria. We found that the need to access medical treatments leads some trans people to approach the diagnosis strategically. While almost all trans people were in favour of the depathologisation of gender dysphoria and at the same time were against its demedicalisation, mainly for instrumental reasons, a few demonstrated contrasting positions whether by agreeing with the idea of gender dysphoria as a pathology or by rejecting medicalisation. The study offers a more nuanced perspective on gender dysphoria than that described in previous sociological and transgender literature.